The Influence of Internal and External Factors on Growth Profits: Case Study of Food and Beverage Companies listed in 2022 Indonesian Stock Exchange - Saefudin, Didin; Yulia, Iis Anisa; Wahidhani, Eha (Institut Bisnis dan Informatika Kesatuan, 2024)
This study aims to determine the influence of internal and external factors on the profit growth of food and beverage companies listed on the Indonesian Stock Exchange in 2022. Internal factors are represented by the debt to equity ratio and current ratio and external factors are represented by inflation and interest rates. The population of this research is 44 companies and the research sample is 22 companies using purposive sampling technique. Data collection techniques are through documentation techniques by downloading financial reports via idx.co.id and the company website. Data analysis used descriptive statistical tests, classical assumption tests, multiple linear regression tests, coefficient of determination tests, t tests and f tests. The research results prove that partially the debt to equity ratio and inflation have a significant negative effect on growth, while the current ratio and interest rates have no effect on profit growth. Simultaneously the debt to equity ratio, current ratio, inflation and interest rates influence profit growth Keywords: Debt to Equity Ratio, Current Ratio, Inflation, Interest Rate, Profit Growth